Experimental exploration of the amphoteric defect model by cryogenic ion irradiation of a range of wide band gap oxide materials. (21st September 2020) - Borgersen, J; Vines, L; Frodason, Y K; Kuznetsov, A; von Wenckstern, H; Grundmann, M; Allen, M; Zúñiga-Pérez, J; Johansen, K M
Abstract: The evolution of electrical resistance as function of defect concentration is examined for the unipolar n -conducting oxides CdO, β -Ga2 O3, In2 O3, SnO2 and ZnO in order to explore the predictions of the amphoteric defect model. Intrinsic defects are introduced by ion irradiation at cryogenic temperatures, and the resistance is measured in-situ by current–voltage sweeps as a function of irradiation dose. Temperature dependent Hall effect measurements are performed to determine the carrier concentration and mobility of the samples before and after irradiation. After the ultimate irradiation step, the Ga2 O3 and SnO2 samples have both turned highly resistive. In contrast, the In2 O3 and ZnO samples are ultimately found to be less resistive than prior to irradiation, however, they both show an increased resistance at intermediate doses. Based on thermodynamic defect charge state transitions computed by hybrid density functional theory, a model expanding on the current amphoteric defect model is proposed.